Purification and Characterization of Phenolic Antioxidant from Corncob Liquid Smoke - Suryanto, Edi; R.I. Taroreh, Mercy; Irma Momuat, Lydia (Asian Journal of Chemistry, 2020)
This study aimed to purify and characterize the antioxidant activity of liquid smoke acquired from corncobs. The smoke of crude liquids was generated through pyrolysis and was purified through fractional and simple distillation. The liquid smoke was analyzed using crude fibres, cellulose, hemicellulose, lignin, antioxidant activity and total phenolic compounds. Gas chromatography-mass spectrometry (GC-MS) was employed to analyze the volatile compounds of liquid smoke. Fractional distillation exhibited the higher carbonyl and phenol content than simple distillation, and the overall acid content of fractional distillation was relatively lower. Moreover, the liquid smoke obtained from fractional distillation exhibited the higher total antioxidant and free radical scavenging activity than simple distillation. The GC-MS results showed different derivatives and phenolic compounds as the most dominant components of the liquid smoke of corncobs. The major antioxidant components of fractional distillation include 2-methoxyphenol, phenol, 2,5-dimethylphenol, 2-methylphenol, 2-methoxy-4-methylphenol, 4-ethyl-2-methoxyphenol and 4-ethylphenol, and those of simple distillation include phenol, 2-methylphenol, 2-methoxy- phenol, 2,6-dimethoxyphenol and 3-ethylphenol.